2022
DOI: 10.1108/oir-06-2021-0299
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream, on-demand and social media consumption and trust in government handling of the COVID crisis

Abstract: PurposeThis study examined the association between media consumers' attitudes toward COVID-19-related content on mainstream, on-demand and social media and trust in the government's ability to handle the pandemic crisis.Design/methodology/approachThe study is based on an online survey of a representative sample of 1,005 Israelis aged 18 and over and focused on consumers' perceptions of media contents as a source of information, social solidarity, criticism and anxiety.FindingsFindings indicate that mainstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Media consumption. The media consumption about COVID-19 can increase trust in governmental actions [41] and compliance with prevention measures [42], but on the other hand, can induce state anxiety when it is excessive [43,44]. Indeed, in our study, we found that more frequent access to COVID-19-related information was positively associated with support for restrictive policies.…”
Section: Plos Onementioning
confidence: 45%
“…Media consumption. The media consumption about COVID-19 can increase trust in governmental actions [41] and compliance with prevention measures [42], but on the other hand, can induce state anxiety when it is excessive [43,44]. Indeed, in our study, we found that more frequent access to COVID-19-related information was positively associated with support for restrictive policies.…”
Section: Plos Onementioning
confidence: 45%
“…“Slacktivism” is term used in the literature (Kwak et al ., 2018; Lim, 2013) to describe the passive use of likes and comments in response to social media memes, which requires little effort and minimum investment of time (Kwak et al ., 2018). Previous research has established a correlation between the portrayal of governmental affairs in the media and a reduction in the level of confidence the populace has in the administration, concomitant with an escalation in their apprehension, during the COVID-19 pandemic (Laor and Lissitsa, 2022). One might have anticipated the employment of social media by the public as a tool for urging action, given the aforementioned downturn in trust in governmental procedures; however, contrary to this hypothesis, this current study reveals a contradictory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The issue gets acute when such content becomes viral within minutes (Pop et al, 2022;L az aroiu and Adams, 2020). Past studies have identified social media as a potential source of dissemination of crisis-related information (Paul and Das, 2022;Laor and Lissitsa, 2022). Social media users were found instantaneously reporting events with videos and photos in the case of natural disasters (i.e.…”
Section: Literature and Hypotheses Developmentmentioning
confidence: 99%